Challenges and Opportunities Encountered by the Master of Arts in Educa-tion (MAED) Students in Cotabato City - Dangalao, Tong Kabenbelan (Future Science / FSH-PH Publications, 2023)
This study aimed to determine the needs and problems in conducting research among the MAED students of Higher Education Institutions in Cotabato City Graduate Schools. It utilized the descriptive–quantitative type of research, and it was conducted in the selected college and universities-graduate schools in Cotabato City. The study's respondents were the forty-four (44) Master of Arts in Education graduating students for 2015-2016. The study employed total enumeration as a sampling technique. A survey questionnaire was generated upon reviewing the related literature and other secondary sources such as research articles and journals. The study's statistical tools used frequency and percentage counts, mean, and the grand mean. The needs of the MAED students in conducting research were perceived as